RESPON KRITIS ATAS PERTANYAAN “APAKAH BUDDHA MENGAJARKAN KELAHIRAN KEMBALI?” - Medhācitto, Tri Saputra (Jurnal Pencerahan, 2022)
The theory of rebirth is widely accepted in Indian philosophy and it is mostly connected with the soul which keeps moving from one life to another life. Since the Buddha rejects the concept of the eternal soul by presenting Anatta theory, many questions are risen whether the Buddha teaches rebirth. Some people assume that the Buddha accepts the doctrine of rebirth because it is popular in pre-Buddhist traditions. This present research purpose is to give a critical explanation of the question of whether the Buddha teaches rebirth. This research is carried out with a library approach by collecting information from canonical texts as well as their commentaries. This research results from a comprehensive explanation of rebirth taught by the Buddha which is very unique and different from the theory of rebirth explained by other Indian traditions. The theory of rebirth (punabbhava) taught by the Buddha neither has an association with any external authority such as Brahma, Jagadātma, or God, nor with any internal entity such as ātma, pudgalātma, or soul. The teachings dealing with rebirth are found in many discourses, especially interconnected with a theory of Karma.